2019
DOI: 10.1093/condor/duz048
|View full text |Cite
|
Sign up to set email alerts
|

Variable effects of a changing climate on lay dates and productivity across the range of the Red-cockaded Woodpecker

Abstract: Many temperate bird species are breeding earlier in response to warming temperatures. We examined the effects of climate on breeding phenology and productivity in 19 populations across the range of the Red-cockaded Woodpecker (Dryobates borealis), an endangered species endemic to pine (Pinus spp.) forests in the southeastern United States. Red-cockaded Woodpeckers nested earlier in warmer springs and delayed nesting in wetter springs. Earlier nesting and larger group sizes resulted in higher productivity. Spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Similarly, researchers could select more biologically relevant sets of candidate variables than the ones presented here. For example, snow cover is likely to be an important variable in several of the case studies (e.g., McNulty, 2018; Wadgymar et al, 2019), however, others were conducted in areas with no snow cover data (e.g., DeMay & Walters, 2020; Lightfoot, 2021) and for consistency we did not include snow in the models.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, researchers could select more biologically relevant sets of candidate variables than the ones presented here. For example, snow cover is likely to be an important variable in several of the case studies (e.g., McNulty, 2018; Wadgymar et al, 2019), however, others were conducted in areas with no snow cover data (e.g., DeMay & Walters, 2020; Lightfoot, 2021) and for consistency we did not include snow in the models.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond a positive effect of warm years on the number of fledglings, we found that weather did not significantly affect productivity. The effects of precipitation and temperature on avian productivity varies in the literature, with most studies detecting no effect of these climate variables (Demay & Walters, 2019 ; Desante & Saracco, 2021 ; Gullett et al, 2015 ). However, some studies noted negative effects of heavy rainfall and low yearly temperatures on fledgling success (Ahola et al, 2009 ; Fisher et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal weather patterns have profound effects on plant and insect communities, and thus on the breeding birds that rely on them (Barnett & Facey, 2016 ; Desante & Saracco, 2021 ; Ladwig et al, 2016 ). While several studies have examined the impacts of breeding season precipitation and air temperature on bird energetics (Haftorn & Reinertsen, 1985 ; Ortega‐Jiménez et al, 2010 ; Schifferli et al, 2014 ), nest provisioning and division of labor (Barras et al, 2021 ; Low et al, 2008 ; Radford et al, 2001 ), nestling growth (Imlay et al, 2017 ; Kruuk et al, 2015 ; Pérez et al, 2016 ), productivity (Demay & Walters, 2019 ; Fisher et al, 2015 ; Gullett et al, 2015 ), and insect abundance (Cucco & Malacarne, 1996 ; Grüebler et al, 2008 ), few studies considered the effects of precipitation and temperature outside of the breeding season on the breeding ecology of insectivorous birds (Desante & Saracco, 2021 ). In the temperate forests of the southwestern United States, year‐round precipitation plays an important role in determining plant communities and overall forest health (Arizpe et al, 2020 ; Kaufmann et al, 2007 ; Sheppard et al, 2002 ; Truettner et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Larger groups contain more non-breeding adult helpers that have been previously shown to improve reproductive success 54 . Part of this benefit is because helpers buffer various aspects of reproduction from environmental factors that have adverse effects on groups without helpers 55 , 56 . It may be that these other factors mask the benefits of cavity orientation in smaller groups.…”
Section: Discussionmentioning
confidence: 99%